2022
DOI: 10.1038/s41427-022-00444-x
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic heptapeptide-based hydrogel boosts the healing of chronic skin wounds in diabetic mice and patients

Abstract: The combined use of peptides, nanomaterials, and hydrogels is a promising strategy for chronic skin wound healing, which remains a huge clinical challenge. Here, we optimized the RL-QN15 peptide, which was shown to be a pro-healing drug candidate in our previous research, to obtain the cyclic heptapeptide (CyRL-QN15) with considerable therapeutic potency against skin wounds. Furthermore, a Zn2+-crosslinked sodium alginate (ZA) hydrogel containing hollow polydopamine (HPDA) nanoparticles loaded with CyRL-QN15 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…An experimental model of type 2 diabetes mellitus (T2DM) was established in C57BL/6 mice ( n = 38) using a high‐fat diet and multiple low‐dose injections of streptozotocin (STZ). In brief, after 4 weeks of a high‐fat diet, mice were weighed (25–30 g), then injected intraperitoneally with STZ (Sigma‐Aldrich, MO, USA) at 30 mg/kg for six consecutive days after overnight fasting 20 . In SD rats ( n = 22), T2DM was induced by a combination of high‐fat diet and intraperitoneal injection of STZ.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental model of type 2 diabetes mellitus (T2DM) was established in C57BL/6 mice ( n = 38) using a high‐fat diet and multiple low‐dose injections of streptozotocin (STZ). In brief, after 4 weeks of a high‐fat diet, mice were weighed (25–30 g), then injected intraperitoneally with STZ (Sigma‐Aldrich, MO, USA) at 30 mg/kg for six consecutive days after overnight fasting 20 . In SD rats ( n = 22), T2DM was induced by a combination of high‐fat diet and intraperitoneal injection of STZ.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, after 4 weeks of a high-fat diet, mice were weighed (25-30 g), then injected intraperitoneally with STZ (Sigma-Aldrich, MO, USA) at 30 mg/ kg for six consecutive days after overnight fasting. 20 In SD rats (n = 22), T2DM was induced by a combination of high-fat diet and intraperitoneal injection of STZ. In brief, rats were housed alone in plastic cages and fed a high-fat diet for four weeks, followed by intraperitoneal injection of STZ (50 mg/kg) for two consecutive days after overnight fasting to induce T2DM.…”
Section: Diabetic Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the MNPs/Cy RL-QN15 /FeCMCS hydrogel holds potential as an innovative agent for promoting wound healing. This potential stems from multiple advantageous properties, including the efficacy of the Cy RL-QN15 peptide in wound healing enhancement, 28 encapsulation and photothermal bactericidal activity of MNPs, and porous architecture of the hydrogel, allowing for the homogeneous dispersion of the physical characteristics of MNPs. In vivo and in vitro investigations demonstrated that the MNPs/Cy RL-QN15 / FeCMCS hydrogel facilitated the regeneration and remodeling of chronically infected wounds by efficiently eliminating both Gram-positive and Gram-negative bacteria, enhancing keratinocyte proliferation and migration, and expediting reepithelialization and collagen deposition.…”
Section: Performance Of the Composite Hydrogel In Woundmentioning
confidence: 99%
“…32 The loading rate and slow-release rate were measured according to previous studies. 25,28 The rheological characteristics of the MNPs/ Cy RL-QN15 /FeCMCS hydrogel, with or without NIR, were analyzed using a rheometer (Anton Paar MCR 302, Austria). Frequency sweep measurements were conducted at 25 °C with a fixed strain of 0.5%.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%